Peran Genetik dan Lingkungan dalam Diabetes Gestasional: Systematic Review - Dwi Lestari, Yusri; Ayu Wulandari, Putri (NHM PRESS, 2024)
Gestational diabetes mellitus (GDM) is a condition that arises during pregnancy due to impaired glucose metabolism. Its development is influenced by a complex interaction between genetic and environmental factors. Genetic factors, such as insulin resistance and glucose metabolism, alongside environmental influences including diet, physical activity, air pollution, and stress, play significant roles in increasing GDM risk. This analysis is based on a literature review examining the relationship between genetic factors, environmental factors, and their interaction in GDM risk. The review includes data from studies on lifestyle, environmental exposures, and underlying genetic mechanisms contributing to GDM development. Research indicates that unhealthy lifestyles, such as high-fat diets and physical inactivity, significantly exacerbate GDM risk in individuals with a genetic predisposition. Environmental exposures, such as air pollution and stress, further deteriorate glucose metabolism through epigenetic changes. These interactions demonstrate that both genetic and environmental factors simultaneously contribute to the elevated risk of GDM. A deeper understanding of the interplay between genetic and environmental factors offers valuable insights for the prevention and management of GDM. Personalized strategies emphasizing healthy lifestyles and mitigating environmental exposures could be effective approaches, particularly for individuals with high genetic risk.